Perceptions of Returnees Concerning Their Rehabilitation and Reinstatement in Swat District, Pakistan: An Evaluative Study - Rafiq, Muhammad; Hassan, Asan Ali Golam; Saeed, Muhammad (Journal of Population and Social Studies [JPSS], 2022)
This article examines the perception of returnees about their reinstatement and rehabilitation in the Swat District of Pakistan. A satisfaction tool, consisting of various domains and indicators, was used for measuring the returnee’s perceptions at two periods, i.e., before rehabilitation (BR) and after rehabilitation (AR). Data were elicited through a self-administered structured questionnaire from 382 samples drawn from the 47,943 Kabal Tehsil, Swat population. Data were analyzed through descriptive and inferential statistics. The findings depict that the value of all the domains increased by 25.7%. The paired sample t-test results show a rejection of all the null hypotheses, indicating a significant increase in the overall satisfaction of returnees in the AR period. The findings indicate that in the AR period, the highest increase occurred in SWL (Satisfaction with Life) domain and the lowest in GOV (Government). This study concludes that the satisfaction of returnees can be further improved by focusing on the domains with a lower level of satisfaction, such as the Government and Social Support domains. Additionally, the tool adopted in this study is significant for measuring the satisfaction level of the distressed population in Pakistan and beyond.